When Leadership Transforms, Engagement Follows: The Mediating Role of Psychological Well-Being among Administrative Staff in Ghanaian Higher Education - Kwofie, Faustina; Ankoma-Sey, Vera Rosemary; Quansah, Nathaniel; Apagya-Quayson, Adriana; Aikins, Philip (PT. Riset Press International, 2025)
The study investigated the relationship between transformational leadership (TL), psychological well-being (PWB), and work engagement (WE) with a specific focus on the mediating role of psychological well-being. Anchored in an explanatory research design, the study involved 104 administrative staff members from the University of Cape Coast (UCC). Data were analysed using descriptive statistics and inferential methods, particularly mediation analysis. Correlation results revealed a moderately significant positive relationship between TL and EPW, as well as between TL and WE. Furthermore, EPW was found to significantly mediate the link between TL and WE, highlighting its critical role in fostering employee engagement. This implies that for higher education institutions, improving leadership alone is not enough; there must also be efforts to create a healthier work milieu where staff members feel valued, less stressed, and more satisfied. Both important theoretical and practical implications have been discussed.